Does Digital Competence Improve Employee Performance? The Role of Smart Digital Services Mediation in the Public Sector - Nawawi, Syarif; Ingsih, Kusni; Riyanto, Fery; Sari, Raden Ayu Aminah Rizkia Puspita; Sartika, Mila (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
This study examines the role of digital competence in improving employee performance, with smart digital services as a mediating variable in the public sector. Previous studies have largely focused on the direct relationship between competence and digital performance, with limited attention to the mediation mechanisms of smart digital services in government agencies. This study addresses this gap by proposing an integrated model that is tested in the context of provincial government. The object of this study was employees of the Regional Secretariat of Central Java Province, with a total of 142 respondents selected using proportional random sampling. The results of the study show that digital competence has a significant positive effect on employee performance, both directly and indirectly through smart digital services. Smart digital services partially mediate the relationship between digital competencies and employee performance, highlighting their strategic role in supporting digital transformation in the public sector. This research contributes theoretically by expanding the digital competency literature through a mediation mechanism model and provides practical implications for public organizations in strengthening digital capacity to improve performance.